The Effect Of Coffee Consumption on Sleep Quality - Kimberly Fiona Retandy; Pricilla Yani Gunawan (Universitas Pelita Harapan, 2025)
Introduction: Faculty of Medicine students frequently experience academic pressure and commonly consume coffee to improve alertness. Excessive coffee consumption or consumption at inappropriate times can result in sleep difficulties, disrupt deep sleep stages, and negatively impact the overall quality of nightly rest. Methods: This study investigates the impact of coffee consumption on sleep quality among students. This research employs a cross-sectional design utilizing categorical comparison. Medical students with no history of sleep disorders were included in the study. Data collected include demographic data, Perceived Stress Scale (PSS-10) questionnaire, Pittsburgh Sleep Quality Index (PSQI), and coffee consumption habits questionnaire. Results: Analysis of 96 samples revealed that in the low coffee consumption group, 35 respondents (36.5%) exhibited mild sleep disturbance, while 17 respondents (17.7%) demonstrated moderate-heavy sleep disturbance. In the moderate-high coffee consumption group, 22 respondents (22.9%) presented with mild sleep disturbance, and an equal number showed moderate-heavy sleep disturbance. There were no association between coffee consumption and sleep quality (p =0.131). Conclusions: There were no significant association between coffee consumption and sleep quality in medical students.Keywords: Coffee consumption, sleep quality, medical students